"OUR HANDS SEEK FREEDOM": HISTORY TEACHING AND THE CHALLENGES OF TEACHER TRAINING IN THE LICENCIATURA DA EDUCAÇÃO DO CAMPO PROGRAM, BOM JESUS (PI), 2023 (VERUM: Journal of Scientific Initiation, 2024)
This article analyzes the pedagogical practices of history teaching in the Licenciatura em Educação do Campo program at the Federal University of Piauí, at the Professora Cinobelina Elvas campus in Bom Jesus (PI). The research includes a literature review on history teaching and rural education, drawing on works by Aragão (2020), Pimenta and Lima (2006), Bittencourt (2008); and Caldart, Pereira, Alentejano, and Frigotto (2012), along with a case study based on the supervised internship report conducted by students. The study highlights pedagogical practices, challenges faced by students, and future perspectives in teacher training in the field of history. It concludes that critical and contextualized training is essential to promote an education that values local culture and the students from rural communities.
Keywords: History teaching; Field education; Teacher training; Supervised internship